1989
DOI: 10.1103/physrevlett.62.1876
|View full text |Cite
|
Sign up to set email alerts
|

Observation of differences between low-energy electron- and positron-diffraction structural determinations of the cleavage faces of CdSe

Abstract: Low-energy positron diffraction (LEPD) is used in conjunction with low-energy electron diffraction (LEED) to determine the relaxed atomic geometries of the CdSe cleavage surfaces. The LEPD analyses yield optimal fits at smaller top-layer perpendicular relaxations than LEED for both cleavage faces, and significantly better agreement between theoretical and experimental intensity profiles.During the past decade, low-energy electron diffraction (LEED) has become a powerful tool for the structural determination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 13 publications
(7 reference statements)
2
12
0
Order By: Relevance
“…In addition, the bond length of the topmost insurface bond is again contracted by 4-7%. This trend is also found for non-polar surfaces of zincblende and wurtzite II-VI semiconductors [54][55][56].…”
Section: Surface Relaxationsupporting
confidence: 51%
“…In addition, the bond length of the topmost insurface bond is again contracted by 4-7%. This trend is also found for non-polar surfaces of zincblende and wurtzite II-VI semiconductors [54][55][56].…”
Section: Surface Relaxationsupporting
confidence: 51%
“…Some examples include new measurements of the Ps ground state hyperfine interval that may solve the long-standing discrepancy between theory and experiment [81], the resolution of the (perhaps related) positronium "lifetime puzzle" [82,83], advances in positron scattering from atoms and molecules [84][85][86], antihydrogen research [87][88][89][90], positron beam [91][92][93] and trap [66,69] development, materials science [65,94], and surface physics [95] (including positron diffraction [96,97] and positron induced Auger emission [98,99]). These areas, and others, will not be discussed here.…”
Section: Introductionmentioning
confidence: 99%
“…This is a counting-based detection system, which obtains the position of the particles incident on the MCP, and has a limited allowance of ∼100 ns for the time between two hits. In this time range, ∼10 5 slow-e + exist in the primary beam, and those could cause a multi-hit problem in this set-up. To address this issue, a pulse stretcher was incorporated.…”
Section: B Pulse Stretcher For a Linac-based Slow-positron Beam Withmentioning
confidence: 94%
“…They developed an electrostatic slow-positron beam with a radioisotope (RI) source emitting positrons through β + -decay. The Brandeis group also demonstrated that in LEPD, experimental intensity profiles were more closely reproduced by the dynamical diffraction theory than in LEED [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%